2022
DOI: 10.1111/anec.12936
|View full text |Cite
|
Sign up to set email alerts
|

Torsade de pointes caused by citalopram during the pacemaker battery‐depletion phase: A case report

Abstract: Pacemaker battery depletion is a gradual process that is usually divided into two stages: elective replacement indication and end of life (Bian et al., 2020). To prolong administration of working hours during the first stage, modifications to the procedures of pacemaker are required (Bian et al., 2020;Crépeau-Gendron et al., 2019). The first phase can last many months, providing a perfect opportunity to replace the pacemaker and epicardial leads (Crépeau-Gendron et al., 2019). If the pacemaker is not replaced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…In the initial medication evaluation, we found that amiodarone, dofetilide, fluconazole, propofol, and sotalol were significantly associated with unadjusted increased risk for diLQTS (Table 1 and Table S1 in Multimedia Appendix 1). Interestingly, medications previously highly associated with inpatient diLQTS, such as haldoperidol [5], methadone [8], citalopram [28], and azithromycin [29], were either borderline or not significantly associated with diLQTS. Additionally, it was noteworthy that ondansetron [30] was significantly associated with a decreased risk of diLQTS (P=1.12 × 10 -39 ).…”
Section: Initial Drug Analysismentioning
confidence: 94%
“…In the initial medication evaluation, we found that amiodarone, dofetilide, fluconazole, propofol, and sotalol were significantly associated with unadjusted increased risk for diLQTS (Table 1 and Table S1 in Multimedia Appendix 1). Interestingly, medications previously highly associated with inpatient diLQTS, such as haldoperidol [5], methadone [8], citalopram [28], and azithromycin [29], were either borderline or not significantly associated with diLQTS. Additionally, it was noteworthy that ondansetron [30] was significantly associated with a decreased risk of diLQTS (P=1.12 × 10 -39 ).…”
Section: Initial Drug Analysismentioning
confidence: 94%